2016
DOI: 10.1038/srep30857
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol modulates facial stimulation-evoked outward currents in cerebellar Purkinje cells in vivo in mice

Abstract: Acute ethanol overdose can induce dysfunction of cerebellar motor regulation and cerebellar ataxia. In this study, we investigated the effect of ethanol on facial stimulation-evoked inhibitory synaptic responses in cerebellar Purkinje cells (PCs) in urethane-anesthetized mice, using in vivo patch-clamp recordings. Under voltage-clamp conditions, ethanol (300 mM) decreased the amplitude, half-width, rise time and decay time of facial stimulation-evoked outward currents in PCs. The ethanol-induced inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, we found that facial stimulation induced LTD at MLI-PC synapses (MLI-PC LTD), accompanied with a decrease in the stimulation-evoked pause of spike firing in PCs via activation of NMDA receptors in the mouse cerebellar cortex, suggesting that sensory stimulation evoked MLI-PC GABAergic synaptic plasticity may play a critical role in motor learning of living animals (Bing et al, 2015). Moreover, acute application of EtOH inhibits the facial stimulation evoked MLI-PC synaptic transmission (Cui et al, 2014), and significantly depresses the MLI-PC synaptic transmission by activating presynaptic cannabinoid receptors via the protein kinase signaling pathway, suggesting that EtOH modulates GABA release from MLIs onto PCs (Wu et al, 2016). Our previous studies suggest that the cerebellar MLI-PC synapse is a target of EtOH, and EtOH consumption may impair the MLI-PC synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that facial stimulation induced LTD at MLI-PC synapses (MLI-PC LTD), accompanied with a decrease in the stimulation-evoked pause of spike firing in PCs via activation of NMDA receptors in the mouse cerebellar cortex, suggesting that sensory stimulation evoked MLI-PC GABAergic synaptic plasticity may play a critical role in motor learning of living animals (Bing et al, 2015). Moreover, acute application of EtOH inhibits the facial stimulation evoked MLI-PC synaptic transmission (Cui et al, 2014), and significantly depresses the MLI-PC synaptic transmission by activating presynaptic cannabinoid receptors via the protein kinase signaling pathway, suggesting that EtOH modulates GABA release from MLIs onto PCs (Wu et al, 2016). Our previous studies suggest that the cerebellar MLI-PC synapse is a target of EtOH, and EtOH consumption may impair the MLI-PC synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the inhibitory conductance, Palmer et al used two-photon uncaging of an intracellular NMDA receptor antagonist (tc-MK801) to locally manipulate NMDA receptors in single branches of tuft dendrites [ 164 ]. These studies with intracellular perfusion of antagonists precisely confirm the impact of specific channel conductance, whereas extracellular drug application enables us to activate/silence channel conductance in a wider range [ 165 , 166 , 167 , 168 ] (but see [ 169 ] for extracellular but greater local drug delivery to patched neurons).…”
Section: Hybrid Methodologies With In Vivo Whole-cell Recording Tementioning
confidence: 73%
“…Paired-current pulses (0.2 ms, 10-100 µA; duration: 50 ms; 0.05 Hz) were used for parallel ber stimulation. For inhibiting postsynaptic PKA in some experiments, protein kinase inhibitor-(6-22) amide (PKI) was added in pipette internal solution [30]. Recordings of mEPSCs were performed in the presence of a mixture of gabazine (20 µM) and tetrodotoxin (TTX; 1 µM) [31].…”
Section: Electrophysiological Recordings [29]mentioning
confidence: 99%